Employability of Teacher Education Graduates of an Asian Public University - Helen Bihag Boholano (Philippine Association of Institutions for Research, Inc., 2012)
The employability of graduates from an institution is very important to note. It is through education and proper training that one may get a decent job after graduation. This study intends to show the employability of teacher education graduates in an Asian public university. The methodological approach was both quantitative and qualitative. Interviews were semi-structured and used a standard set of questions; however graduates were encouraged and motivated to share stories and explain how and why they had arrived at their conclusions and to describe any relevant experiences in the workplace. The findings reveal that the graduates who specialized in English, Mathematics and Sciences are academically talented and motivated group with considerable aspirations to be the teaching model. The study also highlights that Science majors are the most employable graduates while Mathematics majors able to handle other learning areas such as Computer Education and Economics. Many Mathematics major graduates can diversify further through postgraduate studies, either into research or advanced courses in Mathematics in order to be promoted an also for professional and academic growth. It is therefore concluded that there are three top priorities in the workplace for graduates, these includes: challenging/interesting work, a high salary and professional growth.